PENGARUH PERGAULAN TERHADAP KENAKALAN âABGâ DI YOGYAKARTA MENGGUNAKAN REGRESI LOGISTIK - Ridayati, Ridayati (Sekolah Tinggi Teknologi Adisutjipto, 2015)
Junior and Senior High School is the period for what we called unstable of âAnak Baru Gede (ABG) â. Application of high technology like internet, is the ordinary things for students of Junior and Senior High School in Yogyakarta, which is used for doing their homework. Nevertheless, high tech is usedfor looking friends through Facebook, Twitter, etc as well. Nowadays, ABG are always curious of the new things, that lead them to inappropriate research. Even more, lack of parents concern is impacted to immoral behavior. Besides, negative environment gives the fundamental factor to immoral behavior as well. Hence, it effected to mentally and morally degradation. The objective o f this research is for identifying the role of society to ABGs mischievousness in Yogyakarta. This research is used qualitative approach with case study s methodology to obtain data and description related to ABG s mischievousness in Yogyakarta. Next, is using Logistic Regression analysis to analyze the connection. The result is Y=4. 7451.054 X equation. Hence, it concluded that increased one unit of societys role will decrease the degree of ABG s mischievousness by 1.054.